Accuracy of a high‐intensity focused ultrasound device with and without real‐time visualization system in face and neck treatment of skin laxity. (20th June 2020) - Vachiramon, Vasanop; Techakajornkeart, Rattiya; Leerunyakul, Kanchana; Chayavichitsilp, Pamela
Abstract: Background: Microfocused ultrasound (MFU) is a nonsurgical treatment for the improvement of skin laxity. Multiple MFU devices with and without a visualization system are commercially available. Aims: This study aims to compare the accuracy rates of MFU on target treatment areas with and without a visualization system. Patients/Methods: A cross‐sectional study was conducted using 52 dermatologists as study subjects. Each subject was asked to treat one simulated volunteer on the face and upper neck with MFU for 2 sessions using the training mode. Participants were allowed to see the ultrasound monitoring screen in one session (visualized session) and were not allowed to see the monitoring screen in the other session (nonvisualized session). One investigator evaluated the accuracy rate by monitoring real‐time whether an appropriate contact between the transducer and the skin is shown on the visualization system when the energy release button is pressed. Results: Higher accuracy rates were observed in the visualized session than the nonvisualized session in all treatment areas including brow, lateral orbit, infraorbital, cheek, and upper neck. The greatest difference in accuracy rates was observed when performing the treatment on the upper neck. Participants with more experiences had higher accuracy rates while performing visualization session when compared to those who had less experiences. Visualized sessions required a significantly longer treatment time. Conclusions: The utilization of MFU with visualization system increases the likelihood of proper skin contact. This in turn may give a more favorable treatment outcome and decrease the rates of complications from MFU treatment.